Neurological care and risk of hospital mortality for patients with myasthenia gravis in England. Issue 4 (13th August 2007) - Hill, M; Ben-Shlomo, Y
Abstract : Background: Myasthenia gravis (MG) is a rare neurological disorder, which can be life threatening. Although death is a rare outcome, evidence does not exist as to whether neurological care leads to any better outcome than care by other specialties. Methods: A matched nested case control study sampled from all public sector hospital admissions in England with a primary diagnosis of MG from 1991 to 1999. Cases were defined as MG admissions which resulted in death and controls were other MG admissions, matched on sex, age (±2 years) and date of admission (±20 days) that were non-fatal. From a total of 18 251 finished consultant episodes with a mention of MG, we were able to create 196 matched sets with 196 fatal admissions and 788 control admissions. Results: Admission under a neurologist was associated with a 69% reduced risk of death (OR 0.31, 95% CI 0.22 to 0.44; p<0.001). This was only slightly attenuated after adjustment for a variety of patient related and hospital covariates (OR 0.37, 95% CI 0.23 to 0.62; p<0.001). Conclusions: This is the first evidence that patients admitted with MG are far less likely to die if they are under the care of a neurologist. We cannot determine whether this is because of better management per se or because neurologists are usually based in specialist centres and may have better intensive care support, or both. Alternatively, this may be a result of "selection bias" so that neurologists select less seriously ill patients.